(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The study aimed at analysing the Indigenous Water Management Practices in Jama’are LGA of Bauchi State. A total of 400 questionnaires were administered in Ten (10) wards of the study area using Cluster sampling, technique and interviews. The data generated was analyzed using both descriptive and inferential statistics (Dependent sample t-test. The Weighted Criteria Matrix (WCM) was also used as qualitative tool in the study. The study identified five (5) types of indigenous water management practices which are Groundwater harvesting (Lalalo), Runoff harvesting (Tafki and Bingi), Rooftop harvesting (Indororo) and Shadoof (Jigo). The result of the t-test indicates that lalalo, Bingi and Indororo have significant differences in water availability between dry and wet season while for Tafki there is no significant differences in water availability between dry and wet season. For the ANOVA test the result indicated that there is no significant difference in water level between the five studied districts. From the analysis of the WCM which revealed that runoff harvesting practices are more productive and sustainable practices. The study recommends buffering of water sources, formulation of policies and regulations toward the use of indigenous water management practices, advocacy, and improvement of rooftop harvesting, enhancement of community participation in water development programmes